Effect of straw retention and mineral fertilization on P speciation and P-transformation microorganisms in water- extractable colloids of a Vertisol - S. Bai; S. Bai; Y. Ge; D. Yao; Y. Wang; J. Tan; J. Tan; S. Zhang; Y. Peng; X. Jiang (Biogeosciences)
Water-extractable colloids (WECs) serve as crucial micro-particulate components in soils, playing a vital role in the cycling and potential bioavailability of soil phosphorus (P). Yet, the underlying information regarding soil P species and P-transformation microorganisms at the microparticle scale under long-term straw retention and mineral fertilization is barely known. Here, a fixed field experiment (∼ 13 years) in a Vertisol was performed to explore the impacts of straw retention and mineral fertilization on inorganic P, organic P, and P-transformation microorganisms in bulk soils and WECs through a sequential extraction procedure, P K-edge X-ray absorption near-edge structure (XANES), 31P nuclear magnetic resonance (NMR), and metagenomics analysis. In bulk soil, mineral fertilization led to increases in the levels of total P, available P, acid phosphatase (ACP), high-activity inorganic P fractions (Ca2-P, Ca8-P, Al-P, and Fe-P), and organic P (orthophosphate monoesters and orthophosphate diesters) but significantly decreased the abundances of P-cycling genes including P mineralization, P-starvation response regulation, and P uptake and transport by decreasing soil pH and increasing total P. Straw retention had no significant effects on P species and P-transformation microorganisms in bulk soils but led to increases in organic carbon, total P, and available P concentrations in WECs. Furthermore, compared with mineral fertilization, straw retention caused significantly greater differences in the relative abundances of P-cycling genes between WECs and bulk soils. The abundances of phoD gene and phoD-harboring Proteobacteria in WECs increased significantly under straw retention, suggesting that the P-mineralizing capacity increased. Thus, mineral fertilization reduced microbial P-solubilizing and mineralizing capacity in bulk soil. Straw retention could potentially accelerate the turnover, mobility, and availability of P by increasing the nutrient contents and P-mineralizing capacity at the microscopic colloidal scale.